2017
DOI: 10.1007/s10815-017-0998-z
|View full text |Cite
|
Sign up to set email alerts
|

Temporal expression of cumulus cell marker genes during in vitro maturation and oocyte developmental competence

Abstract: The study revealed noticeable differences in the cumulus gene expression profile at different stages of IVM between ovine oocytes of differential developmental ability. The results indicated that the loss of cumulus gene expression along the maturation period in the poor oocytes was related to their intrinsic poor quality in the ovarian follicle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…In buffalo OOs during the NBS, a decreased expression of heat shock protein family A (Hsp70) member 1A (HSPA1A), known to be related to oocyte survival and apoptosis, was also observed. The HSPA1A plays a critical role through its protective action against apoptosis and its expression is reduced in poor, as compared to competent, ovine COCs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In buffalo OOs during the NBS, a decreased expression of heat shock protein family A (Hsp70) member 1A (HSPA1A), known to be related to oocyte survival and apoptosis, was also observed. The HSPA1A plays a critical role through its protective action against apoptosis and its expression is reduced in poor, as compared to competent, ovine COCs 46 .…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h IVM, denuded oocytes were fixed in 4% paraformaldehyde (in 1X phosphate-buffered saline, PBS) and stained with Hoechst 33342 (10 mg/mL) to label oocyte chromatin and determine oocyte meiotic status, as detailed elsewhere [78,79]. Briefly, oocytes at germinal vesicle, germinal vesicle breakdown, metaphase I, and anaphase I stages were considered to be immature.…”
Section: Analysis Of Oocyte Nuclear Meiotic Maturation Stagesmentioning
confidence: 99%
“…Researchers previously localized SCD mRNA via in situ hybridization in rats and found that SCD was associated with human chorionic gonadotropin, FSH, corpus luteum, and granulose cell proliferation [ 29 , 30 ]. STAR is involved in steroidogenic activity of ovaries and is expressed in CCs via the LH surge [ 31 , 32 ]. STAR was showed to be involved in the mitogen-activated protein kinase activity that regulates steroidogenesis in COCs [ 33 ].…”
Section: Discussionmentioning
confidence: 99%